Penentuan Program Indonesia Pintar (PIP) Pada Siswa Kurang Mampu dengan Metode Preference Selection Index (PSI) Berbasis Web - Nelly Khairani Daulay; Asep Toyib Hidayat; Shelfia Shepty (Bulletin of Computer Science Research, 2023)
The Indonesia Smart Program (PIP) is a scholarship assistance provided to individuals with the aim of continuing their education as tuition assistance. This program is the government's idea to reduce the high number of children who drop out of school due to lack of funds. This high dropout rate will also later lead to a high crime rate because children who drop out of school cannot work properly. To determine whether or not students are eligible to receive the Indonesia Pintar Program, a decision support system (SPK) is needed that can provide input for schools to assess properly, which students really deserve the scholarship. By using the Preference Selection Index (PSI) method, it is hoped that this method will be able to select the best alternative from a number of alternatives based on criteria from predetermined aspects.  In the Preference Selection Index (PSI) method which is used as a measure of assessment is the value of alternatives, matrix normalization, average performance value, preference variation value, preference value deviation, criteria weight, calculate the final value, and determine the ranking that will determine the optimal alternative, namely students who are entitled to a scholarship.  The purpose of this research is to determine which students are eligible and not eligible to receive assistance from the government in the form of PIP. The results of this study are in the form of rankings with the highest value of 0.7686 and ranked first or rank 1 and the lowest value of 0.7091 is ranked 5th.